PROFIL PENDERITA SEPSIS AKIBAT BAKTERI PENGHASIL ESBL - Irawan, Danny; -, Hamidah; -, Purwati; EA, Triyono; -, Bramantono; V, Arfianto; U, Hadi; -, Nasronudin; -, Suharto; E, Soewandojo (journal of internal medicine, 2012)
Extended Spectrum !-Lactamases (ESBL) is plasmid enzyme which catalyzing hydrolysis and inactivation !-lactamantibiotic, including third generation of Cephaloporin, penicillin and aztreonam. This enzyme is mutation of !-lactamaseTEM-1, TEM-2, and SHV-1 which commonly found in Enterobacteriaceae and normally have resistance to penisillin andrst generation celaphorin. The incidence of infection cause by ESBL bacterial is increasing worldwide. AntimicrobialResistance in Indonesia: prevalence and prevention (AMRIN study) is showed incidence of infection ESBL bacterial 29%E. coli, and 36% K. pneumonia. This study is descriptive and restrospectively learn about prole of DMK with septicemiapatient caused by ESBL bacterial in Internal Medicine Ward RSUD Dr Soetomo within 1st January 2010 until 30th June2011. Sixty four patient were recruited and 48 patients with ESBL bacterial positive. Mortality rate is 16.7%, severe septiccondition 27.08%, septic shock 14.58%. The result of positive ESBL bacterial was found from urine culture (37.5%).Sensitivity of antibiotics results are meropenem (98.07%), amikacin (88.46%).